Synthesis, characterization and optimization of PVDF/PEBAX composite membranes for CO2/CH4 separation - Mohamad Syafiq, Abdul Wahab (2018)
Biomass such as animal manure, kitchen waste, garden waste, or even human excreta are among the major source of biogas and it contained 60% of methane along with 40% of carbon dioxide. Besides its widely known as a renewable energy sources, methane also contributes to greenhouse gases. Membrane among the vast growing purification techniques that comes to cater this problem by securing the methane gas for energy usability. The current industrial grade Thin Film Composite (TFC) membranes suffer the loss of permeability due to the material limitation. Polyether block amide (Pebax 1657) selective layer was introduced in this research to enhance the separation efficiency of Polyvinylidene fluoride (PVDF) membrane for a low-cost biogas separation, robust and sturdy for prolong application, and a maximum permeate of biogas separation. PVDF was used in this study as a porous substrate layer to the TFC. Pebax 1657 with unique characteristic, possesses both excellent permeability properties from the polar structure and provide good mechanical stability for the TFC. Objective of this research was to develop, characterize, evaluate and optimize the TFC. The development of the TFC was based on two main factors which is the effect of selective layer thickness (1 layer – 4 layers) and effect of casting temperature (27 ºC – 80 ºC). The combination of best selective layer thickness (3 layers) and best casting temperature (60 ºC) have surpassed the Robeson 2008 trade off limit with CO2 permeability and selectivity of 393.92 barrer and 59.23 respectively. Fractional Factorial Design (FFD) screening was employed in this study to minimize the influenced factors during film preparation; selective layer concentration, coagulation bath temperature, evaporation times and quenching times. The two most influenced factors towards the final separation efficiency was found out to be the evaporation times and the selective layer concentration. The optimization study of Central Composite Design (CCD) showed an improvement in selectivity up to 65.75 with an error margin less than 5% indicate that the model of this experimental design can be used for selectivity prediction of any condition in this scope of study.